Growth Hormone Receptor Controls Adipogenic Differentiation of Chicken Bone Marrow Mesenchymal Stem Cells by Affecting Mitochondrial Biogenesis and Mitochondrial Function - Zhao, Changbin; Hu, Bowen; Liao, Zhiying; Wei, Haohui; Zhao, Yongxia; Liang, Jinping; Luo, Wen; Nie, Qinghua; Luo, Qingbin; Zhang, Dexiang; Zhang, Xiquan; Li, Hongmei (Frontiers in Cell and Developmental Biology, 2022)
Growth hormone receptor (GHR) can activate several signaling pathways after binding to growth hormone (GH) to regulate cell growth and development. Sex-linked dwarf (SLD) chickens, normal protein functions are prevented because of exon mutations in the GHR gene, have more severe fat deposition. However, the specific molecular mechanisms responsible for this phenotype remains unclear. We therefore investigated the effect of the GHR gene on adipogenic differentiation of chicken bone marrow mesenchymal stem cells (BMSCs). We found that bone marrow fat deposition was more severe in SLD chickens compared to normal chickens, and the expression of genes related to adipogenic differentiation was enhanced in SLD chicken BMSCs. We also detected enhanced mitochondrial function of BMSCs in SLD chickens. In vitro, overexpression of GHR in chicken BMSCs increased mitochondrial membrane potential but decreased reactive oxygen and ATP contents, oxidative phosphorylation complex enzyme activity, and mitochondrial number. Expression of genes associated with mitochondrial biogenesis and function was repressed during adipogenic differentiation in chicken BMSCs, the adipogenic differentiation capacity of chicken BMSCs was also repressed. With knockdown of GHR, opposite results were observed. We concluded that GHR inhibited adipogenic differentiation of chicken BMSCs by suppressing mitochondrial biogenesis and mitochondrial function.